Online Mindfulness Training Increases Well-Being, Trait Emotional Intelligence, and Workplace Competency Ratings: A Randomized Waitlist-Controlled Trial - Nadler, Ruby; Carswell, Julie J.; Minda, John Paul (Frontiers in Psychology, 2020)
A randomized waitlist-controlled trial was conducted to assess the effectiveness of an online 8-week mindfulness-based training program in a sample of adults employed fulltime at a Fortune 100 company in the United States. Baseline measures were collected in both intervention and control groups. Following training, the intervention group (N = 37) showed statistically significant increases in resilience and positive mood, and significant decreases in stress and negative mood. There were no reported improvements in the wait-list control group (N = 65). Trait mindfulness and emotional intelligence (EI) were also assessed. Following the intervention mindfulness intervention participants reported increases in trait mindfulness and increases on all trait EI facets with the exception of empathy. The control group did not report any positive changes in these variables, and reported reductions in resilience and increases in negative mood. Finally, both self and colleague ratings of workplace competencies were collected in the intervention group only and provided preliminary evidence that mindfulness training enhanced performance on key leadership competencies including competencies related to decisiveness and creativity. The present study demonstrates the effectiveness of an online-based mindfulness training program for enhancing well-being, self-perceptions of emotional intelligence, and workplace performance.